Digitalization as an Alternative Pillar: Moderation of Economic Constraints on IHDI in OIC Countries - Dedi Mardianto; Ina Safitri (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
This study aims to analyze the role of digitalization as a moderator variable in the relationship between economic limitations and the Islamic Human Development Index (IHDI) in the Organization of Islamic Cooperation (OIC) countries. The main problem raised is the low achievement of IHDI and the non-optimal use of digitalization in supporting human development. This study uses a quantitative approach with panel data from 2010 to 2023, with a sample consisting of 10 OIC countries that have complete and representative data. The analysis model used is moderated regression analysis (MRA) with the Fixed Effect Model (FEM) approach.The results show that economic limitations have a positive and significant effect on IHDI. While digitalization does not have a direct effect, it is able to strengthen the effect of the economy on IHDI as a moderating variable. Thus, digitalization can be an alternative pillar in Islam-based human development, especially in the midst of fiscal constraints and social inequality. Therefore, OIC countries need to integrate economic development strategies with digital transformation that is inclusive and based on maqāṣid al-sharī'ah to create sustainable social justice.